Characterization and pathogenicity of Rhizoctonia spp isolated from various crop species in different agroecosystems in Malaysia - Rashed, Osamah Zaid Ali (2017)
Rhizoctonia species is well known as a necrotrophic soilborne fungus prevalent in different agro-ecosystem worldwide. It has been reported as a destructive fungal pathogen that caused various types of diseases on a wide variety of crops. This study investigated Rhizoctonia isolates obtained from different crops and locations based on morphological traits, pathogenicity, molecular identification and genetic diversity characterization. Morphological traits revealed that majority of the isolates were multinucleated (MNR) except for two isolates were binucleated (BNR). Radial growth rate showed that all the isolates could cover the plate within 2-3 days and few isolates covered the plate within four days. Mycelium width ranged between 3.60 -7.33μm, while most of the culture texture appeared oppressed. Nevertheless, some were raised and fluffy. The culture colors were varied from white to light yellowish white or light brown to brown. Sclerotia color was light brown to dark brown and sclerotia distribution pattern was centered and rim concentrated to scatter while the intensity of sclerotia was high to low and some isolates did not produce. Based on identification of the ITS rDNA and tef-1 α genes different taxonomic groups were determined. Twenty-seven isolates were identified as R. solani AG-1 IA, four isolates as R. solani AG-1 ID, two isolates as R. solani AG-4 HG-I and one isolates as R. solani AG-2-2 IV. Two isolates were identified as binucleate Rhizoctonia AG-Fa and AG-A. Phylogenetic analysis using different algorithms separated Rhizoctonia spp. to the distinct clades. Binucleate Rhizoctonia AG-Fa clustered with R. solani isolates indicating close relationship with some taxonomic groups of R. solani. Variation was detected for ITS rDNA and tef-1 α gene sequences at 0.25 variation and 30% homopolymer level. This led to the identification of 50 SNPs and Indels for ITS while 28 SNPs and Indels were found for tef-1 α which indicated that ITS rDNA variation is greater than tef-1 α. Species-specific primer of ITS rDNA region has confirmed the identity of each anastomosis groups. The virulence among isolates of AG-1 IA was varied where strains of rice were more virulent than the strains of corn. Similarly, the virulent among various anastomosis groups in this study showed that AG-1 IA, AG-4 GH-I and AG-2-2 IV were more virulent than AG-1 ID, AG-Fa and AG-A. Genetic variability was detected using RAPD, iPBS and ISSR markers. All molecular markers were able to show reasonable polymorphisms. There was no relationship between morphological traits, pathogenicity, geographical origin and genetic diversity. However, the clustering tree and PCA plot supported the separation based on taxonomic groups indicating that there are other factors which could play a significant role on genetic variation. The knowledge gathered in this study would be useful for developing crops that are resistant to Rhizoctonia diseases. This will assist in planning for the right crop rotation and proper disease management programs.